THE IMPACT OF SOCIAL EMOTIONAL LEARNING INSTRUCTION ON 21 MIDDLE SCHOOL EFL LEARNERS’ OPTIMISTIC THINKING AND RELATIONSHIP SKILLS - Hadjer GHOUGALI; Mostefa MEDDOUR (Analele Universităţii din Craiova. Psihologie, Pedagogie)
The integration of Social Emotional Learning (SEL) principles across various school curricula contributes to the continuous process of enhancing learning through creating a caring and positive learning climate that foregrounds learners’ emotional well-being and emphasizes both academic growth and fundamental life skills. However, relatively few studies have been conducted to explore its impact on middle level students’ performance and its influence on the specific domain of FL/SL learning. The current quasi-experimental study investigates the influence of Strong Kids Curriculum on two of the core competencies of 21 Algerian middle school English as a Foreign Language (EFL) students, precisely optimistic thinking and relationship skills. The results indicate a major improvement in both competencies, with a highly notable difference between pre- and post-intervention values. Additionally, the research indicated major improvement in students’ socialemotional knowledge as well as a high degree of the curriculum implementation fidelity. Most students perceived Strong Kids curriculum as socially valid. The findings offer informative data, which may assist EFL middle school teachers in Algeria to create a positive learning climate that nurtures the personal and academic development of their students in the future.